Recent reductions in the size of facial pigmented basal cell carcinoma at diagnosis and the surgical margin: A retrospective and comparative study. Issue 5 (6th January 2021) - Mae, Kenichiro; Tsuboi, Ryoji; Irisawa, Ryokichi; Sato, Toshitsugu; Fukushima, Noritoshi; Harada, Kazutoshi
Abstract: The present, retrospective, single‐center study analyzed various factors associated with primary basal cell carcinoma (BCC) in the period before and after the introduction of dermoscopy (BD and AD, respectively). The demographic data of patients with primary BCC between 2001 and 2005 (BD: 84 patients, 90 cases) and 2011 and 2018 (AD: 297 patients, 320 cases) were analyzed. In the pigmented BCC‐predominant cohort (94%), the proportion of smaller tumors as well as the total number of tumors significantly increased during AD (median tumor size, 10.0 mm in BD, 8.0 mm in AD; Mann–Whitney U ‐test, p = 0.011). BCC were excised with a significantly narrower margin during AD (median, 2.0 mm) than during BD (median, 3.0 mm; Mann–Whitney U ‐test, p < 0.001; odds ratio, 0.30; multivariate logistic regression analysis, p < 0.001); the incomplete excision rate was 1.9%, and the recurrence rate was 0%. The present study suggests that the introduction of dermoscopy might have aided in the early diagnosis of smaller BCC, especially in the face region, and determining the appropriate surgical margin. The smaller pigmented BCC can be excised with a narrower margin than stated in the guidelines (4 mm).